A fatal case of repeated ventricular fibrillation due to torsade de pointes following repeated administration of metoclopramide. Issue 8 (9th August 2022) - Watanabe, Yusuke; Nakamura, Itaru; Takebayashi, Yasuyuki; Watanabe, Hidehiro
Abstract: Although metoclopramide has many adverse effects, torsade de pointes (TdP) is rare. We describe a fatal case of repeated ventricular fibrillation due to TdP following repeated administration of metoclopramide. Administration of multiple doses of metoclopramide over a short time to a patient with risk factors for TdP should be avoided. Abstract : Although metoclopramide has many adverse effects, torsade de pointes (TdP) is rare. Repeated administration of metoclopramide in combination with risk factors for TdP may cause ventricular fibrillation following TdP.